Influence of a Rotational Speed Modulation System Used With an Implantable Continuous‐Flow Left Ventricular Assist Device on von Willebrand Factor Dynamics. Issue 9 (11th January 2016) - Naito, Noritsugu; Mizuno, Toshihide; Nishimura, Takashi; Kishimoto, Satoru; Takewa, Yoshiaki; Eura, Yuka; Kokame, Koichi; Miyata, Toshiyuki; Date, Kazuma; Umeki, Akihide; Ando, Masahiko; Ono, Minoru; et al.
Abstract: We have developed a rotational speed (RS) modulation system for a continuous‐flow left ventricular assist device (EVAHEART) that can change RS in synchronization with a patient's electrocardiogram. Although EVAHEART is considered not to cause significant acquired von Willebrand syndrome, there remains a concern that the repeated acceleration and deceleration of the impeller may degrade von Willebrand factor (vWF) multimers. Accordingly, we evaluated the influence of our RS modulation system on vWF dynamics. A simple mock circulation was used. The circulation was filled with whole bovine blood (650 mL), and the temperature was maintained at 37 ± 1°C. EVAHEART was operated using the electrocardiogram‐synchronized RS modulation system with an RS variance of 500 rpm and a pulse frequency of 60 bpm (EVA‐RSM; n  = 4). The pumps were operated at a mean flow rate of 5.0 ± 0.2 L/min against a mean pressure head of 100 ± 3 mm Hg. The continuous‐flow mode of EVAHEART (EVA‐C; n  = 4) and ROTAFLOW (ROTA; n  = 4) was used as controls. Whole blood samples were collected at baseline and every 60 min for 6 h. Complete blood counts (CBCs), normalized indexes of hemolysis (NIH), vWF antigen (vWF:Ag), vWF ristocetin cofactor (vWF:Rco), the ratio of vWF:Rco to vWF:Ag (Rco/Ag), and high molecular weight multimers (HMWM) of vWF were evaluated. There were no significant changes in CBCs throughout the 6‐h test period in any group. NIH levels of EVA‐RSM, EVA‐C, and ROTA were 0.0035 ± 0.0018, 0.0031 ± 0.0007, and 0.0022 ± 0.0011 g/100 L, respectively. Levels of vWF:Ag, vWF:Rco, and Rco/Ag did not change significantly during the test. Immunoblotting analysis of vWF multimers showed slight degradation of HMWM in all groups, but there were no significant differences between groups in the ratios of HMWM to low molecular weight multimers, calculated by densitometry. This study suggests that our RS modulation system used with EVAHEART does not have marked adverse influences on vWF dynamics. The low NIH and the absence of significant decreases in CBCs indicate that EVAHEART is hemocompatible, regardless of whether it is operated with the RS modulation system.